Cathelicidin Contributes to the Restriction of Leishmania in Human Host Macrophages - Crauwels, Peter; Bank, Elena; Walber, Bianca; Wenzel, Ulf Alexander; Agerberth, Birgitta; Chanyalew, Menberework; Abebe, Markos; König, Renate; Ritter, Uwe; Reiling, Norbert; van Zandbergen, Ger (Frontiers in Immunology, 2019)
In cutaneous Leishmaniasis the parasitic control in human host macrophages is still poorly understood. We found an increased expression of the human cathelicidin CAMP in skin lesions of Ethiopian patients with cutaneous leishmaniasis. Vitamin D driven, Cathelicidin-type antimicrobial peptides (CAMP) play an important role in the elimination of invading microorganisms. Recombinant cathelicidin was able to induce cell-death characteristics in Leishmania in a dose dependent manner. Using human primary macrophages, we demonstrated pro-inflammatory macrophages (hMDM1) to express a higher level of human cathelicidin, both on gene and protein level, compared to anti-inflammatory macrophages (hMDM2). Activating the CAMP pathway using Vitamin D in hMDM1 resulted in a cathelicidin-mediated-Leishmania restriction. Finally, a reduction of cathelicidin in hMDM1, using a RNA interference (RNAi) approach, increased Leishmania parasite survival. In all, these data show the human cathelicidin to contribute to the innate immune response against Leishmaniasis in a human primary cell model.